2020
DOI: 10.3389/fgene.2020.00881
|View full text |Cite
|
Sign up to set email alerts
|

SlGID1a Is a Putative Candidate Gene for qtph1.1, a Major-Effect Quantitative Trait Locus Controlling Tomato Plant Height

Abstract: Plant height is an important agronomic trait in crops. Several genes underlying tomato (Solanum lycopersicum) plant height mutants have been cloned. However, few quantitative trait genes for plant height have been identified in tomato. In this study, seven quantitative trait loci (QTLs) controlling plant height were identified in tomato. Of which, qtph1.1 (QTL for tomato plant height 1.1), qtph3.1 and qtph12.1 were major QTLs and explained 15, 16, and 12% of phenotypic variation (R 2), respectively. The qtph1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Height is one of the most important agronomic traits for crops, and affects plant architecture, soil utilization rate, nutrition management, and production management [ 1 , 55 ]. In this study, we found that the C2H2 zinc-finger transcription factor SlZF3 regulates tomato plant height via the GA pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Height is one of the most important agronomic traits for crops, and affects plant architecture, soil utilization rate, nutrition management, and production management [ 1 , 55 ]. In this study, we found that the C2H2 zinc-finger transcription factor SlZF3 regulates tomato plant height via the GA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Plant height is one of the most important agronomic traits in crops, which is especially evident in the Green Revolution in cereal crops. It affects crop architecture, land utilization, nutrition, and production management [ 1 ]. Plant height is controlled by many genes, especially those related to plant hormone biosynthesis or signal transduction, including gibberellic acid (GA), auxin, brassinosteroid, and strigolactone [ 2–5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant height (PH) is an important agronomic trait in crops. Height can impact the architecture of plants, nutrient and water management, and mechanical harvest ability, which ultimately affects the quality and yield [ 45 ]. In fresh-market tomatoes, a compact growth habit is desirable because it enables mechanical harvesting [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…PH is a quantitative trait. Several QTLs have been identified related to PH in tomatoes [ 45 ]. A study detected nine QTLs ( ht1 , ht3 , ht5a , ht5b , ht6 , ht7 , ht9 , ht10 , and ht11 ) linked to PH using a segregating population developed from a cross between interspecies tomatoes (vendor Tm-a2 and LA716) [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation